Performance Management of Academic Staff on the Example of the Faculties of Economics in University of Tartu and in Tallinn University of Technology - Kulno Türk; Elar Killumets (Eesti Majanduspoliitilised Väitlused, 2014)
In order to continue its mission in preparing educated work force needed for supporting implementation of Estonian economic policy, universities need to improve the usage of its scarce resources. We study the expectation and attitudes of academic staff towards performance appraisal and related reward systems. Our survey and focus-group interviews revealed that although the systems deployed in those two Universities were different by its nature – Tartu had adopted performance-based approach, where performance appraisal results were closely connected to salary, and Tallinn University of Technology had taken position-based approach, where general salary condition on the time of appointment play pivotal role – the expectations of staff were similar. In both universities, leaders preferred more measurable performance-based systems, but the rest of staff favoured more loose and stable approaches. Implications of results towards appraisal and rewards systems for academic staff are discussed.